Home collection of urine specimens--boric acid bottles or Dipslides?. Issue 3 (March 1990) - Jewkes, F E; McMaster, D J; Napier, W A; Houston, I B; Postlethwaite, R J
Abstract : Sterile mid stream specimens of urine (MSSU) were obtained from 84 children in a hospital outpatient department. All 84 children collected urine at home by one of two Dipslide methods and by collection into boric acid within 24 hours of the hospital collected MSSU. The samples collected at home were posted to the hospital. Thirty six of the Dipslides (43%) and nine of the boric acid samples (10%) were not sterile but none had a pure growth of a single organism of greater than 10(5) organisms/ml. In addition, 17 of the Dipslides (20%) were returned with one or both media detached and therefore could not be relied upon to exclude urinary tract infection. In a second part to the study, 95 urines which showed a significant growth in primary culture were also cultured after storage in boric acid. Inhibition was noted in nine samples after storage in boric acid, seven of which were in underfilled bottles. Transport of specimens in boric acid produced less contamination than Dipslides but may inhibit growth in a small number of specimens. Technical failures with Dipslides were disappointingly high.